FOREIGN FIGURES IN THE PAINTINGS OF I KETUT GEDE SINGARAJA - Purwita Dewa Gede (Badan Riset dan Inovasi Nasional, 2021)
I Ketut Gede Singaraja always portrays figures adopted from the depiction of wayang pattern. It is similar to Wayang Kamasan but more expressive. Aside of painting the local figures, he also painted foreign figures such as Javanese-Muslims, Chinese people, and Europeans. They were narrated as the cultural actors in the life of Singaraja City at the end of the 19th Century. This paper compares those figures, especially their attributes and faces thorugh iconographic studies. The result shows some cultural diversity through figures painted by I Ketut Gede Singaraja. The diversity is a plurality that occurred as a result of cultural unification from the previous period, namely the spice route period. The purpose of this paper is to identify the ethnic foreign figures described by I Ketut Gede Singaraja in his paintings as part of the multicultural life in Singaraja city at the end of the 19th century. I Ketut Gede Singaraja selalu melukiskan figur dengan mengadopsi pola penggambaran wayang yang menyerupai penggambaran wayang Kamasan, akan tetapi lebih ekspresif. Hal yang menarik adalah penggambaran beberapa figur orang asing dalam dua karya lukisan I Ketut Gede Singaraja, yakni figur Muslim-Jawa, figur Tionghoa, figur Eropa dan tentu saja figur lokal yang digambarkan dalam narasi sebagai pelaku budaya di dalam kehidupan Kota Singaraja di akhir abad ke-19. Dalam tulisan ini, dilakukan perbandingan figur, terutama karakter atribut dan wajah melalui studi ikonografi. Hasilnya menunjukan keberagaman budaya melalui figur yang dilukiskan oleh I Ketut Gede Singaraja. Keberagaman tersebut merupakan pluralitas yang terjadi akibat penyatuan budaya pada masa sebelumnya, yaitu pada masa jalur rempah. Tujuannya adalah untuk mengetahui figur-figur asing dari etnis mana saja yang digambarkan oleh I Ketut Gede Singaraja sebagai bagian dari kehidupan multikultur di kota Singaraja.